Recent Developments in the Synthesis of Nitrogen-Containing Heterocycles through C–H/N–H Bond Functionalizations and Oxidative Cyclization - Liu, Xiang; Huang, Yu; Meng, Xu; Li, Jihui; Wang, Dong; Chen, Yongxin; Tang, Dong; Chen, Baohua (Synlett, 2019)
The synthesis and structure of nitrogen-containing heterocycles are fascinating because these compounds have a great richness of structural, physicochemical, and biological properties. Therefore, the development of improved ways for the synthesis of polyfunctional nitrogen-containing heterocycles continues to be a challenging goal. This account describes developments in the discovery of C–H/N–H bond functionalization and oxidative cyclization procedures for the synthesis of nitrogen-containing heterocycles (aziridines, indoles, indolizines, triazoles, imidazoles, oxazoles, thiazoles, quinoxalines, triazines, and pyridines) in our laboratories during the last 15 years.1 Introduction2 Synthesis of Aziridines3 Synthesis of Indoles and Indolizines4 Synthesis of Triazoles5 Synthesis of Imidazoles6 Synthesis of Oxazoles and Thiazoles7 Synthesis of Quinoxalines, Triazines, and Pyridines8 Conclusion and Outlook
Keywords: oxidative cyclization; C–H bond activation; nitrogen heterocycles; N–H bond activation